Wood preservatives / Zulkifli Osman - Osman, Zulkifli (2007)
Wood preservatives have been developed to protect wood and prolong its useful life. Wood preservatives are used in preservation process to give protection from fire, chemical degradation, mechanical wear and weathering as well as biological attack. Three main types of wood preservatives are water borne preservatives, oil type preservatives and organic solvent preservatives. Consequently, wood preservatives can pose an environmental hazard both during use, and when the wood is improperly disposed of.